1966
DOI: 10.5636/jgg.18.157
|View full text |Cite
|
Sign up to set email alerts
|

Geomagnetic Disturbance, Plasma Wind and Solar Activity

Abstract: The authors demonstrate by analysing data for 1960, 1961 and 1962

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1971
1971
1978
1978

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…M regions are the quasi-permanent regions on the sun, devoid of any visible features, to which the 27-day recurrent phenomenon in geomagnetic disturbances has been attributed [Bartels, 1932]. The earlier study of a possible association between the recurrent disturbances and the various characteristic features of active regions in the photosphere, the chromosphere, and the corona led to the controversy as to whether M regions are located in active regions [Mustel, 1964;Sarabhai et al, 1966;Couturier and Leblanc, 1970;Pathak, 1971 ] or tend to avoid them [Saemundsson, 1962;Allen, 1964;Obayashi, 1964;Basler, 1966]. From satellite observations it is now becoming evident that M regions indeed tend to avoid active regions.…”
Section: Introductionmentioning
confidence: 99%
“…M regions are the quasi-permanent regions on the sun, devoid of any visible features, to which the 27-day recurrent phenomenon in geomagnetic disturbances has been attributed [Bartels, 1932]. The earlier study of a possible association between the recurrent disturbances and the various characteristic features of active regions in the photosphere, the chromosphere, and the corona led to the controversy as to whether M regions are located in active regions [Mustel, 1964;Sarabhai et al, 1966;Couturier and Leblanc, 1970;Pathak, 1971 ] or tend to avoid them [Saemundsson, 1962;Allen, 1964;Obayashi, 1964;Basler, 1966]. From satellite observations it is now becoming evident that M regions indeed tend to avoid active regions.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Pai and Sarabhai (1963) and Sarabhai et al (1966) have studied the correlations of 2 5303 intensity with cosmic-ray intensity and Kp and have concluded that regions of enhanced 2 5303 intensity are connected with high velocity solar wind. Brandt and Cassinelli (1966) have suggested that coronal condensations above faculae could be the possible regions connected with solar wind streams of high velocity.…”
Section: Introductionmentioning
confidence: 99%